Berber culture on the world stage : from village to video - Goodman, Jane E., 1956- (Indiana University Press, 2005)
"[S]ure to interest a number of different audiences, from language and music scholars to specialists on North Africa ... a superb book, clearly written, analytically incisive, about very important issues that have not been described elsewhere."--John Bowen, Washington University In this nuanced study of the performance of cultural identity, Jane E. Goodman travels from contemporary Kabyle Berber communities in Algeria and France to the colonial archives, identifying the products, performances, and media through which Berber identity has developed. In the 1990s, with a major Islamist insurgency underway in Algeria, Berber cultural associations created performance forms that challenged Islamist premises while critiquing their own village practices. Goodman describes the phenomenon of new Kabyle song, a form of world music that transformed village songs for global audiences. She follows new songs as they move from their producers to the copyright agency to the Parisian stage, highlighting the networks of circulation and exchange through which Berbers have achieved global visibility.